Application of Survey, Question, Read, Reflect, Recite, and Review (SQ4R) Reading Method in Learning to Read Argumentation Text by Class X Students - Junifer Siregar (research, training and philanthropy institution Natural Aceh, 2023)
The diversity of reading methods does not mean that learning activities must use in various ways. Using a plan that suits the material and needs involves using multiple techniques. This research aimed to obtain the ability to read argumentation texts by students of SMA Negeri 1 Dolok Panribuan using the SQ4R method. The research method used is the experimental method. This research was conducted at SMA Negeri 1 Dolok Panribuan. In particular, the research was carried out in class X. The empirical research design was a group pre-test and post-test design. The research instrument used to obtain data is by using a test. The study results mean that the average value of student learning outcomes in the experimental class before being given less/low treatment and after being given treatment using the SQ4R method increased. This indicates an increase in student learning outcomes after being given treatment. This study aims to improve students' reading skills in understanding argumentation texts and applying the SQ4R method to other texts or discourses.